Computerized Information Systems in the Jordanian Banking Sector: An Empirical Study - Hammoudi, Dalel; Djenane, Abdelhak (مجلة الاقتصاديات المالية البنكية وإدارة الأعمال; No 01 (2012): مجلة الاقتصاديات المالية البنكية وإدارة, 2018)
This study aims at evaluating the existence of the computerized information systems in the Jordanian banking sector, from different aspects. To achieve these objectives, two techniques for gathering data are the questionnaire which represents the primary sources. Books, periodicals and various published studies, represent the secondary sources. The researcher has distributed (164) questionnaires to the users (Accountants and Managers) of the Jordanian commercial banks listed in Amman stock exchange (ASE), (140) were received back and analyzed which represent (85.36%) from the Total population. The results showed that the information technology, and the computer- based financial and accounting systems are highly common in all the Jordanian commercial banks. Finally, the researcher summarized several recommendations according to the conclusions.